Isolation and characterization of a novel human intestinal Enterococcus faecium FUA027 capable of producing urolithin A from ellagic acid - Zhang, Xiaomeng; Fang, Yaowei; Yang, Guang; Hou, Xiaoyue; Hai, Yang; Xia, Mengjie; He, Fuxiang; Zhao, Yaling; Liu, Shu (Frontiers in Nutrition, 2022)
Urolithin A (UA) has received considerable research attention because of its health benefits. However, only a few strains have been reported to produce UA from ellagic acid (EA), and the molecular mechanisms underlying the gut microbiota-mediated transformation of ellagic acid into urolithin A is limited. In the present study, a single strain FUA027 capable of converting ellagic acid into UA in vitro was isolated from the fecal samples. The strain was identified as Enterococcus faecium through the morphological, physiological, biochemical and genetic tests. UA was produced at the beginning of the stationary phase and its levels peaked at 50 h, with the highest concentration being 10.80 μM. The strain Enterococcus faecium FUA027 is the first isolated strain of Enterococcus sp. producing urolithin A from ellagic acid, which may be developed as probiotics and used to explore molecular mechanisms underlying the biotransformation of ellagic acid into UA.